JENDRAL HOEGENG IMAM SANTOSO: KAPOLRI JUJUR, DISIPLIN DAN SEDERHANA SEBAGAI TELADAN GENERASI MUDA - Nur Hidayati; Anny Wahyuni; Budi Purnomo (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2021)
General Hoegeng Iman Santoso was the Chief of the Indonesian National Police (Kapolri) in 1968 - 1971. He is a son of the nation who was born in Pekalongan on October 14, 1921. This research uses the historical research method according to Daliman which consists of four steps, namely: 1) Heurustik ( data collection), 2) Source Criticism (testing), 3) Interpretation (Analysis), 4) Historiography (Writing History). The results of this study are 1) Biography of Hoegeng Iman Santoso 2) Career Tracks of Hoegeng Iman Santoso 3) Hoegeng's characters that can be imitated by the younger generation: a) honesty, namely behavior in an effort that makes him dependable in words, actions and activities, honesty Hoegeng should be used as a role model for the younger generation b) time discipline determines human fluency in achieving something he wants c) simplicity is an act that is in sync with actual conditions.